Wave Information Studies (WIS) Pacific Regional Hindcast - Tracy, B.; Spindler, D. (2008 DoD High Performance Computing Modernization Program Users Group Conference, 2008)
Coastal wave information is invaluable to coastal engineering projects, designs, maintenance of structures, erosion studies and storm climatology analyses. The mission of the Wave Information Studies (WIS) program in the Coastal and Hydraulics Laboratory (CHL), Engineer Research and Development Center (ERDC) in Vicksburg, MS, is to provide a database of wave information for all the United States coastlines. This information is useful in both civil and military applications. WIS populates this wave information database with wave parameter results from a wave hindcast, a process that uses input wind fields over a gridded area (grid points are identified as water with a specific depth or land) as input to a numerical wave hindcast computer code that models all the physical processes produced from ocean wind wave generation for past events. These wave hindcasts produce wave spectral energy information for every grid point and provide a continuous record of wave information. WIS hindcast results are compared with measurements from in-situ buoys for quality control. The WIS website currently contains at least 20 years of recent wave information for stations near the Atlantic, Gulf of Mexico, Pacific Basin, and Great Lakes coastlines. The Pacific Basin hindcast presented special challenges because of the vast area of the basin, the scarcity of measured information, the necessity for accurate propagation of swell energy from North Pacific and southern hemisphere storms over the Pacific basin, and accurate obstruction definition of small islands in the grid. Research and testing of several wave hindcast models resulted in the choice of the WAVEWATCH III (version 2.22 developed at NOAA/NCEP) numerical wave hindcast model for the Pacific Basin hindcast. This numerical hindcast model using state-of-the-art input wind fields from Oceanweather, Inc., produced 23 years (1981-2004) of wave hindcast information for the Pacific Basin. This information has proved to be invaluable for projects in the Hawaiian Islands and American Samoa. The next frontier for WIS is to produce wave information close to the Pacific mainland coastline. Regional Pacific wind fields for five years at a spacing of 0.25 degrees were secured from Oceanweather, Inc., to use with existing basin wind fields for the same time period at 0.5 degree spacing. The WIS CHL staff has collaborated with NOAA/NCEP to use the new multi-grid WAVEWATCH III numerical wave hindcast model to produce a wave hindcast that computes results from three nested grids in one run. This new technology developed and released by NOAA/NCEP late in 2007 allows WIS to run the basin 0.5 degree grid along with two regional grids (0.25 deg and 1/12 deg) covering the Pacific mainland west coast. Energy can move freely in and out of the boundaries of the three nested grids. This complex multi-grid WAVEWATCH III MPI parallel application would not be possible without the parallel computing resources available at the ERDC MSRC. This paper will show the initial results of the hindcast, comparisons of results with measured information, and will give an overview of the computing process for the Pacific regional hindcasts.